Analysis of Stakeholders Regional Innovation Based on Government Collaboration in Indragiri Hilir Regency - Ismail Ismail; Sri Hartati; Dini Adhania; Abd Salam (Journal of Governance, 2022)
Government performance and regional competitiveness can be increased through regional innovation involving various stakeholders. The existence of stakeholders is adjusted to their roles and responsibilities so that the results achieved can run optimally. This study aims to identify the stakeholders involved and analyze their roles based on power and interest. This study uses a qualitative approach with stakeholder analysis techniques. The results of the stakeholder analysis show grouping in two contexts, namely, primary stakeholders, namely, the central and regional governments, as well as secondary stakeholders, consisting of the community, academics, entrepreneurs, and the mass media. To support success in implementing regional innovation, an analysis of the role of each stakeholder is carried out. The results of the analysis show that stakeholders are divided into four categories based on power and interest: subjects, key players, crowd, and contest setters. The division of roles and responsibilities among each stakeholder can accelerate the process of implementing regional innovations in Indragiri Hilir Regency.